External Root Resorption and Caries of Mandibular Second Molar in Association with Third Molar Impaction Status - Bayrak, Seval; Ankaral, Handan; Şahin, Onur; Çakmak, Emine Ş.K.; Demiralp, Kemal Ö. (Journal of Dentistry Indonesia, 2019)
Impaction status of a mandibular third molar (M3) leads to some pathological conditions. Objective: Thisretrospective study was conducted to compare the effect of erupted (e-M3) and impacted mandibular third molars(i-M3) on caries in the adjacent second molar and external root resorption (ERR). Methods: We used cone beamcomputed tomography (CBCT) images of 200 patients with a mean age of 28.19 ± 8.3 years who had an e-M3on one side of the mandible and an i-M3 on the other side of the mandible. All the images were evaluated for theexistence of caries and ERR. Results: Caries was detected in 32.5% of cases of i-M3 and in 21% of cases of e-M3(p = 0.01). ERR was present in 18.5% of cases of i-M3 and no resorption was observed in cases of e-M3 (p = 0.00).Conclusions: Caries and ERR in cases of i-M3 can be reliably identified via CBCT scan. Among patients withcaries in the i-M3 group, the degree of caries was significantly lower on the other side of the mandible. Instead ofprophylactic removal of e-M3, periodic clinical and radiologic examinations are advised.